(untitled) (World Bulletin of Education and Learning, 2026)
This article examines the didactic possibilities of integrated educational technologies in developing the functional literacy of primary school students. In contemporary education, functional literacy is regarded as a key indicator of a learner’s ability to apply acquired knowledge, skills, and competencies in practical life situations. In primary education, this process is especially significant because it forms the basis for further intellectual development, independent thinking, and active participation in the learning process. The study is grounded in the idea that integrated educational technologies create favorable pedagogical conditions for combining subject content, strengthening interdisciplinary relations, and organizing learning activities in a meaningful and learner-centered way. The article analyzes the essence of functional literacy, its structural components, and the pedagogical significance of its development in the early stages of schooling. Particular attention is given to the didactic potential of integrated educational technologies, including problem-based learning, project work, interactive methods, digital tools, and competency-oriented tasks. These technologies are interpreted as effective means for improving reading comprehension, mathematical reasoning, communicative ability, critical thinking, and the capacity to solve real-life educational tasks.